Daclatasvir plus sofosbuvir, with or without ribavirin, is highly effective for all kinds of genotype-2 chronic hepatitis-C infection in Taiwan. Issue 9 (September 2019) - Wu, Sih-Hsien; Chu, Chi-Jen; Su, Chien-Wei; Lin, Chung-Chi; Lee, Shou-Dong; Wang, Yuan-Jen; Lee, Fa-Yauh; Huang, Yi-Hsiang; Hou, Ming-Chih
Abstract : Background: Based on the previously published results, 12 weeks of sofosbuvir (SOF) 400 mg/day plus ribavirin (RBV), the current direct antiviral agent regimen reimbursed by Bureau-of National-Health-Insurance (BNHI) of Taiwan for genotype-2 chronic hepatitis C (CHC), is suboptimal in efficacy, especially for difficult-to-treat subpopulations such as liver cirrhosis, previous interferon (IFN) treatment failure, and high viral-load. This study aimed to evaluate the efficacy and safety of SOF plus daclatasvir (DCV) for Taiwanese genotype-2 CHC patients. Methods: Between March 2017 and December 2018, a total of 50 consecutive genotype-2 CHC patients who completed 12 weeks combination of SOF (400 mg/day) plus DCV (60 mg/day) with or without RBV by investigators were enrolled for analyses. When RBV was added, weight-based (800-1200 mg/day) approach was applied. Sustained virological response (SVR12 ) was defined by undetectable HCV RNA (<15 IU/mL) at the end and 12 weeks after completion of therapy. Results: The mean age was 62.0 ± 11.4 years, 16 (32.0%) of them were males and 20 (40.0%) of them failed to previous IFN. Severity of liver diseases was as follows: ⩽F2 fibrosis: 24.0%; F3 fibrosis: 40.0%, Child-Pugh A cirrhosis: 30.0%; and Child-Pugh B-C cirrhosis: 6.0%. The mean baseline HCV RNA level was 6.19 ± 0.91 log10 IU/mL and 30 (60.0%) had baseline HCV RNA ≥ 2 million IU/mL. The rates of undetectable HCV RNA (<15 IU/mL) at weeks 2, 4, and end-of-treatment were 40%, 94%, and 100%, respectively. Majority (66.7%) of patients with detectable HCV RNA at week 2 belonged to low-level viremia (<50 IU/mL). Subjective adverse events (AEs) and laboratory abnormalities were more common for patients combining RBV. Grades of AEs were generally mild and all patients finished therapy without interruption. After post-treatment follow-up, all 50 patients (100%) achieved SVR12 . Conclusion: Our real-world cohort of Taiwan showed that a 12-week SOF/DCV-based treatment was well-tolerated and highly effective for genotype-2 CHC patients with or without liver cirrhosis.